Evaluasi Kepuasan Pengguna Menggunakan Model End User Computing Satisfaction (EUCS) Pada Valery (Virtual Resources Library) Perpustakaan Universitas Bandar Lampung - Putry, Dhea Nabella; Kesuma, Mezan el Khaeri; Yunita, Irva; Amaliah, Eni (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
By using the End User Computing Satisfaction (EUCS) paradigm, EUCS is a model or method used to measure the level of user satisfaction with an information system by considering several indicators such as content, accuracy, format, ease and timeliness. This study attempts to assess the level of user satisfaction with Valery , a virtual resource library at the Bandar Lampung University Library that has a unique voice feature that makes it interesting to study. By using quantitative techniques, this study is descriptive. In this study, 88 participants were surveyed. Information was collected using a survey using a Likert scale. This study uses the mean and grand mean formulas for data analysis. Finally, the evaluation findings are presented on an interval scale. By using the End User Computing Satisfaction (EUCS) model, the Bandar Lampung University Library evaluated Valery , a virtual resource library, and found that users were generally satisfied with its system with an average score of 4.51. By using the End User Computing Satisfaction (EUCS) model, Valery  (Virtual Resources Library) of Bandar Lampung University Library received a "Very High" rating in the interval range from 4.20 to 5.0. Suggestions and input for further research are: first, it is expected to conduct research with the same theme but with different perception indicators in order to expand again regarding research and the use of the Valery  application, for example reading access by other users: second, the phenomenon of the number of students is inversely proportional to the number of Valery  digital collections and inversely proportional to the number of users who have installed Valery